THE INFLUENCE OF CROWDFUNDING INNOVATION AND TRUST ON ONLINE DONATION DECISIONS ON CROWDFUNDING PLATFORMS - Tarigan, Edi Suranta (Jurnal Apresiasi Ekonomi, 2023)
This study aims to explore the impact of innovation in crowdfunding and the level of trust on donation decisions through crowdfunding platforms. The sampling method used in this research is non-probability sampling. Respondents involved in this study are millennial entrepreneurs who are located in Bandung City and have made donations through crowdfunding platforms. The number of respondents involved in this study was 153 people. The data analysis method used is multiple linear regression with data processing support using IBM SPSS Version 25. The research findings show that innovation in crowdfunding and the level of trust have a positive influence on donation decisions on crowdfunding platforms. The policy implications of the findings of this study are that the government and related institutions can encourage innovation in crowdfunding platforms through incentives and support, strengthen transparency and accountability in fund management, protect donor rights with clear policies, and improve public education and financial literacy. Thus, it is expected to create a healthier, transparent, and trustworthy crowdfunding ecosystem, increasing participation and benefits for all parties involved.